Review. The story of melanocyte: long way from bench to bedside - Shahbazi, Atefeh; Zargar, Seyed Jalal; Motamed, Nasrin; Aghdami, Nasser; Shafieyan, Saeed (Technium BioChemMed, 2022)
Skin is composed of major layers, a superficial epidermis and a deeper dermis. The color of skin is influenced by a number of pigments, including melanin. Melanin is produced by cells called melanocytes. Most skin disorders are relatively benign, but a few, including melanomas, can be fatal. A couple of the more noticeable disorders, namely albinism and vitiligo, affect the appearance of the skin and its accessory organs. Vitiligo is associated with significant psychosocial morbidity and profound effect on quality of life. Topical steroids, calcineurin inhibitors, phototherapy and surgery are most common treatments. However, there are many patients who do not respond to any of these modalities. The transplantation of cultured or non-cultured melanocyte is the most important treatment for hypopigmentory disorders. In this study, we are going to assess the history of melanocyte cultivation and evaluate the effectiveness of transplantation cultured cells. We examined the beginning process of isolation, characterization, and transplantation of epidermal cells. This review, summarize our current understanding of the cutaneous pigmentary system from the start of synthesis in the pigment cells, along with the response of repigmentation. During the production of melanin, melanosomes are transferred to neighboring keratinocyte in order to form perinuclear melanin caps. The objective of this review is to analyze the melanocytes transplantation in the last century up to now, and how epidermal cells can increase pigmentation in hypo-pigmented areas in skin disorders. Also, we focus on the story of the melanocyte back to 1950. In addition, prior systemic therapy was associated with a significant increase significant increase based on combined additional therapy, achieving desired results and improved outcomes. Despite the short study of a long way of melanocyte assessment and follow up patient's treatment, results of the all reports were confirmed the efficacy of the used method in the treatment of stable vitiligo who did not respond to the common algorithms of non-invasive treatments.